ADAPTATION TEST OF FIVE NEW HYBRID MULBERRY TO IMPROVE NATURAL SILK PRODUCTIVITY - Lincah Andadari; Rosita Dewi; Sugeng Pudjiono (Pusbindiklat - LIPI, 2016)
One of the problems faced by silk production in Indonesia is low productivity of mulberry that is currently planted by the farmers. Therefore, it is necessary to develop new hybrid of mulberries that have a higher leaves production. Before the new hybrid of mulberry can be cultivated by farmers, the new hybrid plant should be tested first. Adaptation test is required to view genetic response of the plant with the environment in which mulberry grows. The purpose of this study is conducting adaptation test of mulberry’s five types new hybrid to measure the growth and the productivity of plants. Adaptation test research of mulberry’s five new hybrids has been conducted from 2012 until 2014 in Cipeuteuy Village, Sub District Kabandungan, District of Sukabumi. This research used randomized block design method with six treatments and three replications. The results showed that two types of hybrid mulberry showed high percentage growth on average 99%. The use of hybrid mulberry Morus cathayana x Morus amakusaguwa IV.12 in natural silk production can increase 59,60 % of productivity, while Morus cathayana x Morus amakusaguwa IV.10 can increase 47,83% of productivity. Two types of hybrid mulberry, Morus cathayana x Morus amakusaguwa IV.12 and Morus cathayana x Morus amakusaguwa IV.10 have excellent potential in silkworm feed productivity development.